A thousand metagenome-assembled genomes of Akkermansia reveal phylogroups and geographical and functional variations in the human gut - Lv, Qing-Bo; Li, Shenghui; Zhang, Yue; Guo, Ruochun; Wang, Yan-Chun; Peng, Yongzheng; Zhang, Xiao-Xuan (Frontiers in Cellular and Infection Microbiology, 2022)
A. muciniphila has long been considered to be the only Akkermansia species in the human gut and has been extensively studied. The present study revealed the genomic architecture of Akkermansia in human gut by analyzing 1,126 near-complete metagenome-assembled genomes, 84 publicly available genomes, and one newly sequenced A. glycaniphila strain from human gut. We found that 1) the genomes of Akkermansia were clustered into four phylogroup with distinct interspecies similarity and different genomic characteristics, and 2) A. glycaniphila GP37, a strain of Akkermansia is isolated from the human gut, whereas previously it had only been found in python. Amuc III was presented in Chinese population and Amuc IV was mainly distributed in western populations. A large number of gene of functions, pathways, and carbohydrate active enzymes that specifically associated to phylogroups. Our findings based on over a thousand genomes strengthened the previous knowledge and provided new insights into the population structure and ecology of Akkermansia in human gut.